Treatment of Anterior Teeth Discolorization Post-PSA Using Porcelain Crown: Case Report - Badi Soerachman; Levina Azzahra Rachman (Sean Institute, 2026)
Pulp necrosis is a pathological condition caused by the death of pulp tissue, often due to untreated dental caries. Pulp necrosis can lead to tooth discoloration, which is a major aesthetic complaint for patients. Root canal treatment (ROT) is an essential procedure to remove necrotic tissue and restore tooth function. Crown restoration is necessary to improve the structural strength and aesthetics of teeth that have undergone ROT. This case report discusses a 22-year-old woman who complained of discoloration of her anterior teeth. Clinical and radiographic examinations revealed a diagnosis of pulp necrosis in the left maxillary central incisor. Treatment was performed using conventional techniques, irrigation with 2.5% sodium hypochlorite (NaOCl) solution, intracanal application of calcium hydroxide (Ca(OH)2) medication, and obturation with gutta-percha and sealer. The final restoration was performed with a fiber post and a full porcelain crown (zirconia) to improve retention, strength, and aesthetics of the tooth. This combination of PSA treatment and restoration has been proven effective in maintaining function, preventing fractures, and improving the aesthetics of non-vital teeth, thus providing good long-term results for patients.